CLINICAL FEATURES, MANAGEMENT AND OUTCOMES OF PATIENTS WITH INSULINOMA: A 14-YEAR SINGLE-CENTER EXPERIENCE IN THE PHILIPPINES - Sandoval , Mark Anthony; Magnaye, Franz Michael (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION This study determined the clinical, biochemical, imaging and histopathologic features and subsequent management and outcomes of patients with insulinoma in a tertiary hospital within 14 years. METHODOLOGY In a retrospective review of medical records from 2007 to 2021, 14 patients diagnosed with insulinoma were identified and their pertinent clinical profiles, management, and outcomes were retrieved. Vital status was determined by phone call using the provided contact information after obtaining verbal consent. Descriptive statistics were performed to summarize data. RESULTS Among the 14 patients included, the majority were females (71.43%) with a median age of onset at 48.14±14.7 years. Neuroglycopenic symptoms were the more common presentation rather than adrenergic symptoms. Fasting hypoglycemia was unanimously present. The median onset of hypoglycemia during a 72-hour fast was at 5 hours (IQR 9.06). Median serum insulin [41.8 µIU/mL (IQR 43.57)] was inappropriately normal in the presence of hypoglycemia. Median C-peptide was elevated [6.68 ng/mL (IQR 16.71)]. The use of any combination of diagnostic tests, such as abdominal CT scan, MRI, endoscopic ultrasound and intraarterial calcium stimulation localized 92.9% of the tumors preoperatively. Intraoperatively, tumors were more commonly seen in the head of the pancreas (53.85%), with decreasing frequency in the body (23.08%), neck (15.38%) and tail (7.69%). Most tumors are solitary (85.71%), with a mean tumor largest dimension of 2.04 ± 0.7 cm. They are commonly benign (92.31%). Only one patient had multiple metastatic masses at presentation. Of the five specimens sent for Ki-67 staining, four were found to be moderateto high-grade well-differentiated neuroendocrine tumors. All except one underwent surgery, due to the inability to localize the tumor preoperatively. Among the patients with known vital status (eight out of 14), six were alive without recurrence, while two had died related to insulinoma. CONCLUSION Although insulinoma remains a rare disease, it may present relatively more frequently in specialized centers. While some clinical characteristics were comparable to other cohorts, there were some distinctive features in our setting.